1998
DOI: 10.1002/ana.410440124
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characteristics of myoadenylate deaminase deficiency

Abstract: Two types of myoadenylate deaminase (MAD) deficiency have been described, primary or inherited, and secondary or acquired MAD deficiency. In this study, we investigated whether secondary MAD deficiency is indeed acquired or merely coincidental. We demonstrated the same underlying molecular defect, a C34T transition, in both types of deficiency. Furthermore, the same frequency of the mutant MAD allele was found in the general population as in patients with neuromuscular complaints. We therefore conclude that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
59
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 13 publications
10
59
0
1
Order By: Relevance
“…Moreover, Safranow et al (2009) reported no significant association between SBP and genotype, although DBP was higher in the CC genotype carriers than in the other subjects. In this study, we found a 2% AMPD1 deficiency in the CT (or heterozygous) genotype, which agrees with previous studies (Morisaki et al, 1992;Verzijl et al, 1998). However, our findings from this study were not in general agreement with those of previous researchers, who claimed that AMPD1 polymorphisms have no harmful effect on the human body (Verzijl et al, 1998).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Moreover, Safranow et al (2009) reported no significant association between SBP and genotype, although DBP was higher in the CC genotype carriers than in the other subjects. In this study, we found a 2% AMPD1 deficiency in the CT (or heterozygous) genotype, which agrees with previous studies (Morisaki et al, 1992;Verzijl et al, 1998). However, our findings from this study were not in general agreement with those of previous researchers, who claimed that AMPD1 polymorphisms have no harmful effect on the human body (Verzijl et al, 1998).…”
Section: Discussionsupporting
confidence: 64%
“…C34T (rs17602729), which represents the transition C>T at the 34th nucleotide, is a nonsense mutation that results in the formation of a premature stop codon in the second exon; it is the most common type of AMPD1 polymorphism among Caucasians, with a frequency of 10%-15%. This type of mutation occurs in more than 2% of Caucasian and African-American populations (Morisaki et al, 1992;Verzijl et al, 1998;Toyama et al, 2004;Rubio et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, approximately 2% of Caucasians exhibit a skeletal muscle AMPD deficiency and nearly 20% are carriers of this genetic disorder [1,2] . In the majority of cases this deficiency is due to a nonsense mutation (C34T) in exon 2 of the AMPD1 gene resulting in a premature stop codon and a truncated inactive enzyme [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Absence of MAD occurs in approximately 2% of muscle biopsy submitted to pathologic examination for suspected neuromuscular disease 6 . MAD deficiency have been described in muscle biopsy of patients with polyneuropathy, infantile spinal muscular atrophy, congenita myopathy with type-2 fiber atrophy, facioscapulohumeral myopathy, polymyositis, dermatomyositis, myotonic dystrophy, limb-girdle muscular dystrophy, dystrophinopathies, systemic sclerosis, McArdle's disease, phosphofructokinase deficiency, and hyperornithinaemia with gyrate atrophy of the retina 3,[7][8][9] . MAD deficiency associated with other neuromuscular disorders was previously thought to be the result of a limitation in MAD transcript availability, secondary to the pathological abnormalities in a variety of neuromuscular or rheumatological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…MAD deficiency associated with other neuromuscular disorders was previously thought to be the result of a limitation in MAD transcript availability, secondary to the pathological abnormalities in a variety of neuromuscular or rheumatological disorders. Verzijl et al 7 found that isolated MAD deficiency and MAD deficiency associated with other neuromuscular disorders had the same underlying molecular DNA defect. In the latter cases, MAD deficiency is merely a chance association, due, a concurrence of the frequently occurring mutant MAD allele with another neuromuscular disorder.…”
Section: Discussionmentioning
confidence: 99%